Electro‐Physical Properties of Gate‐Last Silicon MOSFETs with Low‐Temperature SiOxNy/HfOx Stack After Ultra‐Shallow Fluorine Implantation from RF Plasma. Issue 8 (16th May 2018) - Mroczyński, Robert; Jasiński, Jakub
Abstract : Ultra‐shallow fluorine implantation from radio frequency (RF) plasma performed in reactive ion etching (RIE) reactor at room temperature (RT) is adopted to metal‐oxide‐semiconductor field‐effect transistors (MOSFETs) technology on silicon (Si) substrates with gate‐last low‐temperature SiOx Ny /HfOx double‐gate dielectric stack. The implantation technology is optimized in order to get the maximum fluorine concentration very close to the silicon sub‐surface region. The electrical characterization of fabricated structures reveals an improved quality of the semiconductor/dielectric interface, i.e., lower interface state density ( N it ), effective charge ( Q eff ) and, as a consequence, enhanced mobility ( μ eff ) value and lower sub‐threshold swing (SS) of the investigated MOSFETs. The presented findings are promising for possible applications of fluorine implantation from RF plasma in modern semiconductor devices. Abstract : This study presents the feasibility of ultra‐shallow fluorine implantation into silicon sub‐surface region performed in the standard reactive ion etching (RIE) process. The implantation is adopted to the MOSFETs technology with gate‐last SiOx Ny /HfOx double‐gate dielectric stacks. An improved quality of fabricated structures has been observed that makes the RIE implantation a very favorable option for a controllable and repeatable introduction of fluorine ions into Si substrate.